Restriction fragment length polymorphism effectively identifies exon 1 mutation of UGT1A1 gene in patients with Gilbert's Syndrome - Shiu, Tzu-Yue; Huang, Hsin-Hung; Lin, Hsuan-Hwai; Shih, Yu-Lueng; Chu, Heng-Cheng; Chang, Wei-Kuo; Hsieh, Tsai-Yuan (Liver international, 2015)
Background & Aims Gilbert's syndrome causes pharmacological variation in drug glucuronidation and unexpected toxicity from therapeutic agents. The two common genotypes of Gilbert's syndrome are a dinucleotide polymorphism (TA)7 in TATA‐Box as well as the 211G>A mutation in the coding exon 1, particularly in Asians, of human UGT1A1 gene. In this study, we aimed to establish an effective method to detect the 211G>A mutation. Methods The coding exon 1 sequence of human UGT1A1 gene was analysed by Vector NTI software. The 211G>A mutation in the coding exon 1 of UGT1A1 gene was determined by restriction fragment length polymorphism (RFLP) method. Serum total bilirubin level was measured as well. Results A newly identified BsmBI site was located in the coding exon 1 of UGT1A1 gene. The 211G>A mutation in the coding exon 1 of UGT1A1 gene was determined by DNA RFLP. Furthermore, we reported our present work on genetic analysis of mutations of UGT1A1 gene, and the correlation of UGT1A1 mutations with serum total bilirubin levels in Taiwanese population. The results showed that 15 subjects carried 211G>A mutation in 23 subjects related with Gilbert's syndrome. The homozygous 211G>A mutant as well as simultaneously heterozygous mutants both in TATA‐Box and 211G>A significantly increased the risk of Gilbert's syndrome similar to subjects carrying homozygous TATA‐Box mutant. Conclusions BsmBI RFLP is an effective method to detect 211G>A mutation in the coding exon 1 of UGT1A1 gene. The common 211G>A mutation is one of the causes of Gilbert's syndrome in Taiwanese population.